Statistical approach to the computation of an influence of the Yangtze dam on gravity fluctuations - Birylo, Monika; Pajak, Katarzyna (International Conference “Environmental Engineering”, 2017)
Due to the realization of the Three Gorges Dam on the Yangtze River and its content of 40 billion tons of water many geodynamical consequences can still be observed. It is obvious that global geodynamical changes are noticeable at whole basin of the Yangtze river. Such changes can be observed by the GRACE (Gravity Recovery and Climate Experiment) gravimetric satellites (Ilk et al. 2005). The GRACE gravity field model data are available in the form of spherical harmonic expansion; by defining a specific filter, one can compute geoid variations at specific locations. As a reference, EGM2008 model was used, on its basis geoid variations were determined. According to the results, geoid variations at the Yangtze river become more stable after filling the Dam. In the article a statistical methods were used for the purpose of the evaluation of a differences EGM08-GRACE time series in the area of the Three Gorges Dam. In the article the authors want to present trend analysis and short-term forecasting with ARIMA model usage.
Keywords: ARIMA; geoid; GRACE; the Three Gorges Dam